Ethanol Positively Modulates Photosynthetic Traits, Antioxidant Defense and Osmoprotectant Levels to Enhance Drought Acclimatization in Soybean - Md. Mezanur Rahman; Mohammad Golam Mostofa; Ashim Kumar Das; Touhidur Rahman Anik; Sanjida Sultana Keya; S. M. Ahsan; Md. Arifur Rahman Khan; Minhaz Ahmed; Md. Abiar Rahman; Md. Motaher Hossain; Lam-Son Phan Tran (MDPI AG, 2022)
Drought is a major environmental threat to agricultural productivity and food security across the world. Therefore, addressing the detrimental effects of drought on vital crops like soybean has a significant impact on sustainable food production. Priming plants with organic compounds is now being considered as a promising technique for alleviating the negative effects of drought on plants. In the current study, we evaluated the protective functions of ethanol in enhancing soybean drought tolerance by examining the phenotype, growth attributes, and several physiological and biochemical mechanisms. Our results showed that foliar application of ethanol (20 mM) to drought-stressed soybean plants increased biomass, leaf area per trifoliate, gas exchange features, water-use-efficiency, photosynthetic pigment contents, and leaf relative water content, all of which contributed to the improved growth performance of soybean under drought circumstances. Drought stress, on the other hand, caused significant accumulation of reactive oxygen species (ROS), such as superoxide and hydrogen peroxide, and malondialdehyde, as well as an increase of electrolyte leakage in the leaves, underpinning the evidence of oxidative stress and membrane damage in soybean plants. By comparison, exogenous ethanol reduced the ROS-induced oxidative burden by boosting the activities of antioxidant enzymes, including peroxidase, catalase, glutathione S-transferase, and ascorbate peroxidase, and the content of total flavonoids in soybean leaves exposed to drought stress. Additionally, ethanol supplementation increased the contents of total soluble sugars and free amino acids in the leaves of drought-exposed plants, implying that ethanol likely employed these compounds for osmotic adjustment in soybean under water-shortage conditions. Together, our findings shed light on the ethanol-mediated protective mechanisms by which soybean plants coordinated different morphophysiological and biochemical responses in order to increase their drought tolerance.